1999
DOI: 10.1007/s100350050022
|View full text |Cite
|
Sign up to set email alerts
|

Axial particle diffusion in rotating cylinders

Abstract: We study the interface dynamics of a binary particle mixture in a rotating cylinder numerically. By considering only the particle motion in axial direction, it is shown that the initial dynamics can be well described by a one-dimensional diffusion process. This allows us to calculate a macroscopic diffusion constant and we study its dependence on the inter-particle friction coefficient, the rotation speed of the cylinder and the density ratio of the two components. It is found that radial segregation reduces t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 28 publications
2
17
0
Order By: Relevance
“…8, the estimates in Table 1 and the numerical evidence for collapse under Eq. 3 with DðCÞ ¼ 1 þ ðC − 1∕2Þ because T Ã is valid for constant D only, and neither the experimental (35,36) nor the simulated (34,37) data is sufficiently well esolved to specify the form of DðCÞ used here.…”
Section: Resultsmentioning
confidence: 99%
“…8, the estimates in Table 1 and the numerical evidence for collapse under Eq. 3 with DðCÞ ¼ 1 þ ðC − 1∕2Þ because T Ã is valid for constant D only, and neither the experimental (35,36) nor the simulated (34,37) data is sufficiently well esolved to specify the form of DðCÞ used here.…”
Section: Resultsmentioning
confidence: 99%
“…Reported values of D lie in the range 1 × 10 −4 -10.4 × 10 −4 cm 2 /s for drum speeds in the range 10-65 rpm. Dury and Ristow (1999) conducted a numerical study of the interface dynamics of a binary particle mixture in a rotating cylinder. They concluded that the dependence of D with rotation speed ( ) is linear only for low speeds (Hogg et al, 1966) and that a quadratic function gives a better fit when a broader range of rotation speeds is considered.…”
Section: Mixing/dispersion Coefficientmentioning
confidence: 99%
“…Rotary cylinders or kilns are widely used in industry for processes such as mixing, drying, coating and performing chemical reactions. Granular motion within these cylinders is also an area of significant research interest due to the rich array of phenomena exhibited [1][2][3]. Depending on the system conditions, several different flow regimes have been identified within rotating cylinders including: sliding, surging, avalanching, rolling, cascading, cataracting and centrifuging [4,5].…”
Section: List Of Symbolsmentioning
confidence: 99%